Determining Partition Coefficient (Log P), Distribution Coefficient (Log D) and Ionization Constant (pKa) in Early Drug Discovery - S. Bharate, Sonali; Kumar, Vikas; A. Vishwakarma, Ram (Combinatorial Chemistry & High Throughput Screening, 2016)
An early prediction of physicochemical properties is highly desirable during drug discovery to find out a viable lead candidate. Although there are several methods available to determine partition coefficient (log P), distribution coefficient (log D) and ionization constant (pKa), none of them involves simple and fixed, miniaturized protocols for diverse set of compounds. Therefore, it is necessary to establish simple, uniform and medium-throughput protocols requiring small sample quantities for the determination of these physicochemical properties. Log P and log D were determined by shake flask method, wherein, the compound was partitioned between presaturated noctanol and water phase (water/PBS pH 7.4) and the concentration of compound in each phase was determined by HPLC. The pKa determination made use of UV spectrophotometric analysis in a 96-well microtiter plate containing a series of aqueous buffers ranging from pH 1.0 to 13.0. The medium-throughput miniaturized protocols described herein, for determination of log P, log D and pKa, are straightforward to set up and require very small quantities of sample (< 5 mg for all three properties). All established protocols were validated using diverse set of compounds.
Keywords: UV spectrophotometry